Virtual pets want to travel: Engaging visitors, creating excitement. (July 2021) - Thirumaran, K.; Chawla, Shailey; Dillon, Roberto; Sabharwal, Jagdeep Kaur
Abstract: This paper proposes a gamified approach to promote tourism attractions based on users' interaction with a virtual pet in the context of an AR mobile application. Technology Acceptance Model, 6–11 Framework and Persuasive Systems Design are combined, to extract factors influencing the intention to travel with the virtual pet. A survey questionnaire was developed and administered online to 539 participants. Outcomes of this study highlight the significant role of emotional attachment and rewarding experience towards intention to travel with a virtual pet. The outcomes also helped us to develop a new 'Intention to Travel' (I2T) model. To interest and excite prospective visitors, a design of a mobile game with Augmented Reality (AR) features is proposed which will involve engaging interactions with virtual pets to attract visitors to desired location(s). Practitioners such as game developers and tourism policy makers may consider the virtual pets as a vehicle to impact tourists' behavior. Highlights: Gamification of tourist experiences with Augmented Reality (AR) impacts tourist behavior 'Intention to Travel' (I2T) model emerging as a result of study outcomes 'Emotional Engagement' & 'Rewarding Experience' as key factors influencing 'Intention to Travel' Augmented Reality based game concept is proposed to attract tourists